SOFT SKILL DEVELOPMENT TO IMPROVE THE TEACHERS' PROFESSIONAL COMPETENCE IN ISLAMIC EDUCATION PERSPECTIVE - Qonita Fitra Yuni (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
Professional teachers are required to always evolve according to the demands of dynamic change. In the perspective of Islamic education, teachers get high appreciation of the position one level below from the position of the Prophet. The Islamic appreciation of the learned men is illustrated in the hadith as quoted by Ahmad Tafsir (in Hasbullah, 1999: 193), namely: "Ulama's ink is more precious than the blood of the martyrs". The development of soft skill to improve the professional competence of teachers can be done through coaching programs such as upgrading, training/workshops, seminars or scientific meetings, e-learning, or formal activities in accordance with the needs of teachers. The development and fostering of professional competence of the teacher needs to be done continuously and comprehensively, so that will give birth to a comprehensive professional teacher as well.